Kerjasama International Organization for Migration (IOM) dan Pemerintah Indonesia dalam Menangani Perdagangan dan Perbudakan Manusia di Industri Perikanan PT. Pusaka Benjina Resource Tahun 2015 - Diah Ajeng Ariestya Putri; Tri Cahyo Utomo (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
The case of human trafficking in the fishing industry has not been comprehensively identified, and there are no adequate legal instruments, so that the workers on fishing vessels are vulnerable to slavery. The case of human trafficking and slavery in Benjina is the largest case in the fishing industry in the 21st century. The Government of Indonesia seeks to cooperate with IOM to tackle the case so that it can be expected that there will be no more human trafficking and slavery practices in the Indonesian fishing industry. This research aims to analyze the cooperation between the Government of Indonesia and IOM in dealing with human trafficking and slavery in Benjina, by first describing the situation and conditions of human trafficking and slavery that occur in Benjina, the factors that had influenced the victims in the recruitment process, IOM's role in helping the victims, up to the obstacles of the cooperation between the Government of Indonesia and IOM in handling the case. This thesis uses qualitative research methods with explanatory research types and analyzed by collecting data from books, annual reports of government agencies and IOM, and mass media. An explanation of the cooperation between the Government of Indonesia and IOM uses the theory of liberalism. This research concludes that despite there are some obstacle factors, there are also some factors that faciltate the cooperation between the Government of Indonesia and IOM in handling human trafficking and slavery in PT. Pusaka Benjina Resource fishing industry in 2015.